Mapping Water and Sanitation Condition to Improve Universal Access in Bandung City - Hasbiah, Astri Widiastuti; Mulyatna, Lili; Pradiko, Hary; Hidayat, Hidayat; Afiatun, Evi; Racmie, Hermin Aulia; Triani, Nine (Journal of Community Based Environmental Engineering and Management, 2023)
Many developing countries lack the necessary infrastructure for clean water supply and sanitation facilities, especially in urban areas. Cities in Indonesia are also facing this problem. The rapid growth of urban areas puts a strain on existing water and sanitation infrastructure, making it difficult to meet the increasing demand for services. This can lead to inadequate mapping and planning for future needs. Water and sanitation mapping is an important tool for monitoring access to clean water and sanitation facilities to gather accurate data and improving access to clean water and sanitation. The purpose of this study is mapping water and sanitation condition and calculate the sanitation index. The mapping carried out includes source of drinking water, wastewater, drainage system, and solid waste disposal. The study was conducted in RW 06 Pasirluyu, a community neighbourhood in Bandung City. The methods used are questionnaire interviews and direct observation. The total respondents of study locations were 225 houses, but only 101 houses were willing to participate in the study. The study results show that 89% of respondents clean water source comes from deepwell groundwater for cooking and washing, wheran openmain source for drinking water is from bottled water, 89% of respondents use septic tank for their wastewater, 11% of respondents dispose their wastewater into open channels or conduct open defecation, 89% of the draineage is open drainage system, and 61% of the respondents conducted solid waste separation. Sanitation index assessment in RW 06 Pasirluyu calculated scored 1.25 for drinking water aspect, 1.23 domestic wastewater aspect. 1.21 drainage aspect, 1.02 domestic waste aspect. Overall, based on the sanitation index assessment results, the RW 06 Pasirluyu is classified as good.